Community Service to Increase the Investment Literacy Level of Employees in Sukabumi - Peter, Peter; Iskandar, Dini; Martalena, Martalena; Wahyusaputra, Tedy; Herlina, Herlina; Hadianto, Bram (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
The fraudulent investment is everywhere; therefore, society must be watchful. By following up on this situation, the efforts of other parties, such as the Indonesian Financial Authority and the campus, are needed to demonstrate that other legal investment alternatives remain available. As an inseparable part of the campus, lecturers must participate in community service to educate society. Furthermore, the lecturers from Maranatha Christian University visit Sukabumi to educate participants affiliated with BPK Penabur on the relevant subjects. To effectively measure their understanding, this community service uses the advanced multiple-choice questions on financial literacy by Lusardi (2007), distributed via a Google link before and after the materials are presented. As a result, the correct answer portion increases from 62.7193% to 73.4649%.